Dynamic Capabilities and MNE Global Strategy: A Systematic Literature Review‐Based Novel Conceptual Framework - Pitelis, Christos N.; Teece, David J.; Yang, Hongyi (Journal of Management Studies, 2023)
AbstractGlobal strategy cannot be fully understood without consideration of dynamic capabilities (DCs). This is because the three key constituents of DCs – the sensing and seizing of opportunities and the reconfiguration of the resource base – are essential preconditions for strategy development, within nations and cross‐border. We investigate the aspects of DCs that are most suitable for global strategy and those that need to be revisited and developed. We discuss theory and evidence on DCs and global strategy, present a systematic literature review, compare theory and evidence, and identify gaps between the two as well as opportunities to align them more closely and to develop both. To help guide future research, we develop a novel conceptual framework and provide suggestions for more theory‐congruent empirical research.